Laparoscopically Assisted Vaginal Hysterectomy : The Initial 10 Cases, Srinagarind Hospital Experience - Seejorn, Kanok; Buphasiri, Pranom; Ratanasiri, Thawalwong; Sawasdipanich, Acom; Pattamas, Auayporn (Srinagarind Medical Journal, 2013)
Background : Laparoscopically surgery has become more and more popular during recent years. Srinagarind hospital has been offering laparoscopic hysterectomy since February 1996. Objective : To study patient profiles in the initial 10 cases of laparoscopically assisted vaginal hysterectomy (LAVH) at Srinagarind Hospital Study design : A retrospective descriptive study Setting : Department of Obstetrics and Gynecology, Faculty of Medicine, Srinagarind Hospital, Khon Kaen University Subjects : 10 cases with LAVH between February 1996 and July 1996 Main outcome measures : Operating times, techniques for LAVH, 8 cases were myoma uteri, 2 cases were recurrent DUB. The average operating time was 2 hours 27 minutes DUB. The average operating time was 2 hours 27 minutes per case. One case had torn dome of urinary bladder during surgery, repaired by laparoscopic suturing. Conclustion : LAVH is a new technique for gynecologic surgery. It needs gynecologists with more training and requires further study to determine the effectiveness of the procedure Key words : LAVH